Understanding and promoting equitable post-discharge care in firearm injury survivors: a retrospective chart review - Claire L. Jacobson; Rehan Choudhury; Allison Broad; Anna M. Maw; Chelsea Wolf; Brian Adams; Anne Drabkin (Scientific Reports)
Abstract Patients that survive firearm injuries frequently require follow-up care. This study aims to explore demographic characteristics of patients presenting to the emergency department for post-firearm injury care and to understand the reasons for their return visits. This was a retrospective chart review of all emergency department and readmission patient encounters for post-firearm injury care during the study period, January 1, 2019 to December 31, 2022, at an urban safety net hospital. Seventy-four patients with 84 corresponding emergency department encounters were included in the analysis. Key findings were that patients from racial and ethnic minorities, patients insured by Medicaid, and patients experiencing homelessness were overrepresented in the study cohort. Additionally, many repeat emergency department visits were potentially avoidable, stemming primarily from insufficient pain control, wound checks, postoperative complications, and infections. The authors proposed potential interventions to improve post-firearm injury care, including the provision of wound care kits and the optimization of the discharge medication pick-up process.